Implementasi Konsep Arsitektur Berkelanjutan pada Ruang Publik di Kabupaten Purworejo - Maya Puspita Sari; Sri Yuliani (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2024)
The SDGs discuss the need for public spaces in the 11th component, namely the provision of public spaces and green open spaces that are safe, inclusive and easily accessible, especially for women and children, the elderly and people with disabilities. This encourages the planning of a public space in Purworejo Regency which is also in line with the development objectives of Purworejo Regency in the Regional Regulation of Purworejo Regency Number 11 of 2021. This research focuses on identifying and determining design strategies for public spaces with sustainable concepts. The method of theoretical studies with comparative analysis to determine the program and site of public spaces with sustainable concepts, then draw conclusions that produce design strategies. The result of this research is a design strategy for the implementation of sustainable concepts in public spaces in Purworejo Regency.